An optimised simulation of component-based embedded systems in manufacturing industry. (18th December 2008) - Khalgui, Mohamed; Carpanzano, Emanuele; Hanisch, Hans-Michael
This paper deals with an optimised simulation of embedded systems following the international standard IEC61499 in which a Function Block is an event triggered component owning data and an application is a network of blocks that have to satisfy properties described in user requirements. We design these components in different abstraction levels of a hierarchy to control the development complexity. To achieve a feasible simulation, we formalise at first-time the FB concept by defining the Control Function Module (CFM) and the Virtual Plant Module (VPM). We propose thereafter a technique processing temporal deadlines for control modules and we define in the system behaviour critical scenarios where properties can be violated. We apply the simulation around these scenarios by applying a fault injection technique to optimise the system validation and to consider its hierarchy, we propose a simulator architecture based on the master-slave model where a slave injects faults in each level of the hierarchy, whereas the master chooses the best values of these errors to generate critical scenarios.